ARTISTIC INTERPRETATION OF LIBERATION COMPETITIONS OF PERIOD OF THE FIRST WORLD WAR IN STORY p. M.DERLITSYA «MILITARY DIDICH» - Suliatitsky, M. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
In the article introduce analysis of the story – the literary interpretation of national – liberation movement of Ukrainians during the First world war. Show the wide artist palette of the story, the area of literary character create.